Efecto de micorrizas y actinomicetos en el Zeamays l. Cultivado en invernadero - Huamán Ramos, Andrés Pedro (2021)
The objective of this research was to evaluate the effect of mycorrhizals and actinomycetesoncorncultivation, Ccarhuay variety (Zea mays L) in the greenhouse of biological tests of the National University of Huancavelica. The experiment was evaluated using the Random CompletelyBlocksDesign, with 5 treatments (Huachaybamba 1 Micorrized Soil (SMH1), Pomavilca 2 Mycorred Soil (SMP2) Soil withActinomycete of Chupa1 (SACH1),soilwithActinomyceteofPueblo Viejo 2 (SAPV2), and“Común Era” soil,as Witness(T))distributedin5blocks,and25 experimental units. Plant height, stem diameter, number of leaves per plant, root length, vigor index,fresh and dry weight of root and foliar biomass were evaluated. The results indicate that soils with mycorrhizals and actinomycetes do not influence root length, but increase plant height, fresh and dry weight of root biomass.Soilswithactinomycetesincrease thediameterofthestems,therateofvigor, the fresh and dry weight of the foliar biomass of plants of corn.